A alienação da liberdade pela própria liberdade : o paradoxo do problema do mal em Paul Ricoeur - Silva, Janaína Rosa da (2017)
This research aims to investigate the paradox of the problem of evil that alienates freedom through freedom itself. Since Augustine, philosophy has rejected the idea of a nature of evil as a being, as a thing, which, on the one hand, led the understanding of evil to the field of the imperfection of human nature. Modern philosophy places freedom as the central point of discussions around the origin of evil action, especially Descartes, Kant and Hegel. However, imputability and guilt show the limit of the autonomy of the sovereign subject, since the subject is both capable of good and capable of evil. In order to understand the paradox between evil, freedom and the able subject of Ricoeurian, this investigation begins with Ricoeur's Philosophy of Will, in an attempt to show how the capable subject is placed in opposition to the sovereign subject from the realization of the fragility of the will in the face of evil. Then, from the long hermeneutic way as a form of interpretation we seek to understand the meaning of hermeneutical theory of symbols and myths, transmitted by the ancient Babylonian, Jewish and Christian cultures in the works symbolic of evil (1960) and The conflict of interpretations (1969). The relation between evil and freedom in Ricoeur has its genesis in direct dialogue with the problem of radical evil and the free will of Kantian philosophy. In the face of the subject of Ricoeurian who wants to reveal himself as a being that brings to light through the mysterious subjectivity constituted between body and thought a subject of powers. This capable subject is criticized by Levinas with the theory of absolute alterity, which is opposed to the Ricoeurian subjectivity of self-understanding. In the course of our investigation, we note that the subject of powers of Ricoeur, although clothed with a paradox, has the merit of empowering the human being as agent, an agent responsible for his actions. The study of the performative character of freedom without the use of transcendence led us to think of the ransom of forgiveness as a form of restoration of alienated freedom.